2014
DOI: 10.1021/jo502390z
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Promoted Intermolecular Electron Transfer in Tetrathiafulvalene–Thiacalix[4]arene Conjugates and Tetrachlorobenzoquinone

Abstract: In this work, two series of tetrathiafulvalene (TTF) and thiacalix[4]arene (TCA) conjugates (TTF-TCA) were designed by CuAAC click reactions. The results obtained from NMR and (1)H NMR NOE indicated that their conformations of thiacalix[4]arene framework may prefer to 1,3-alternate. The cyclic voltammograms of four TTF-TCA compounds containing electroactive TTF units were provided. Meanwhile, their intermolecular electron-transfer (ET) behaviors with tetrachlorobenzoquinone (Q) mediated by different metal ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Several low rim TTF‐calixarene conjugates were prepared using the click reaction between TTF‐azide and calixarene‐propyne derivatives [116,117] . These receptors were used to study intermolecular electron transfer (ET) to quinone acceptors promoted by the simultaneous complexation of the metal ions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several low rim TTF‐calixarene conjugates were prepared using the click reaction between TTF‐azide and calixarene‐propyne derivatives [116,117] . These receptors were used to study intermolecular electron transfer (ET) to quinone acceptors promoted by the simultaneous complexation of the metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors were used to study intermolecular electron transfer (ET) to quinone acceptors promoted by the simultaneous complexation of the metal ions. In particular, one example of thiacalix[4]arene receptor 12 it was shown that ET between TTF and Q was possible only upon complexation of metal ions (such as Sc 3+ , Pb 2+ , Ag + , Cd 2+ , and Zn 2+ ) between two “legs” on the lower rim of thiacalixarene [117] . Intramolecular ET was investigated using calixarene derivatives with electron donors (TTF) and acceptors (quinone) attached side‐by‐side to the calixarene scaffold [118,119] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redox-inactive metal ions have attracted much attention because they are known to affect the redox behavior of redox active compounds acting as a Lewis acid [1][2][3][4][5][6][7][8][9]. Among such metal ions, scandium ion (Sc 3+ ) shows the strongest Lewis acidity because of the small ionic radius with trivalent positive charge, leading to a significant positive shift of the reduction potentials of compounds [10][11][12][13][14][15][16][17][18][19][20][21][22][23], including metal-oxygen complexes [19][20][21] and radical species [22,23]. Of special interest is the fact that Sc 3+ enables the electrontransfer reactions, which would otherwise never take place in the absence of Sc 3+ , to occur thermodynamically as well as kinetically [10][11][12][13][14][15]20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Among such metal ions, scandium ion (Sc 3+ ) shows the strongest Lewis acidity because of the small ionic radius with trivalent positive charge, leading to a significant positive shift of the reduction potentials of compounds [10][11][12][13][14][15][16][17][18][19][20][21][22][23], including metal-oxygen complexes [19][20][21] and radical species [22,23]. Of special interest is the fact that Sc 3+ enables the electrontransfer reactions, which would otherwise never take place in the absence of Sc 3+ , to occur thermodynamically as well as kinetically [10][11][12][13][14][15]20,21]. We have reported that an electrontransfer disproportionation of 2,2-diphenyl-1-picrylhydrazyl radical (DPPH • ) occurs upon the addition of scandium triflate, Sc(OTf)3 (OTf = OSO2CF3), to an acetonitrile (MeCN) solution of DPPH • to produce one-electron-oxidized and -reduced species of DPPH • , DPPH + , and DPPH − , respectively [23].…”
Section: Introductionmentioning
confidence: 99%